Adult learners in higher education: learner engagement and literacy-related issues - Sarjit Kaur (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
This paper attempts to explore learner engagement and literacy-related issues among adult learners in a higher education context in a public university in Malaysia. 25 final year students in the B.A. English Language and Literature Studies (ELLS) programme in Universiti Sains Malaysia provide insightful comments on their learning experiences and literacy-related issues affecting their academic journey. Based on student responses in focus group interviews and students' journal entries, the paper examines the life stories of these adult learners and their views on learner engagement and literacy. This localized approach aims to provide literacy educators with a more comprehensive understanding of the complexities surrounding adult learners' learning experiences.